Predictive role of Oxford Classification for prognosis in children with IgA nephropathy: a systematic review and meta-analysis - Xiaohang Liu; Chen Wang; Zimo Sun; Man Liu; Nan Zhou (Renal Failure)
Background The Oxford Classification was proposed as an independent prognostic indicator in IgA nephropathy (IgAN). However, most studies on the subject focus on adults instead of children.Objectives Using a meta-analysis to appraise the predictive roles of the Oxford classification for the prognosis of pediatric patients with IgAN.Methods All cohort studies regarding the analysis of the association between poor kidney-related prognosis (GFR categories G2-G5) according to the Kidney Disease Improving Global Outcomes (KDIGO) Guideline in pediatric patients with IgAN and five pathologic lesions in the Oxford Classification were included. Hazard ratios (HRs) regarding the association between the Oxford classification and prognosis of pediatric patients with IgAN were synthesized using random effect models. The risk of bias in studies was assessed based on the Newcastle-Ottawa scale.Results Fourteen articles were included with 5679 IgAN patients and 710 endpoint outcome events occurred. M1 was associated with a higher risk of poor kidney-related prognosis compared with M0, pooled HR (1.79; 95%CI, 1.46–2.19; p < 0.001, random effect model). S1 and T1 or T2 increased the risk of poor kidney-related prognosis (pooled HR, 2.13; 95%CI, 1.68–2.70; p < 0.001; pooled HR, 2.64; 95%CI, 1.81–3.86; p < 0.001, respectively, estimated by random effect model). Compared with C0, C1, or C2 was also associated with an increased risk of poor kidney-related prognosis in the subgroup analysis of Asian and other populations. Evidence to indicate that E1 increased the risk of poor kidney-related prognosis was marginal.